Stress-responsive tomato gene SlGRAS4 function in drought stress and abscisic acid signaling. (March 2021) - Liu, Yudong; Wen, Ling; Shi, Yuan; Su, Deding; Lu, Wang; Cheng, Yulin; Li, Zhengguo
Highlights: SlGRAS4 enhances ROS scavenging under drought stress in tomato. SlGRAS4 directly binds to and activates SlSnRK2.4 promoter. Protein-protein interaction between SlSnRK2.4 with SlAREB1/SlAREB2 were validated. SlGRAS4 confers drought tolerance through SnRK2-AREB pathway in tomato. Abstract: Adverse environmental conditions such as drought stress greatly limit the growth and production of crops worldwide. In this study, SlGRAS4, a drought stress-responsive GRAS gene from tomato ( Solanum lycopersicum ) was functionally characterized. Repressing SlGRAS4 ( SlGRAS4 -RNAi) increased sensitivity to drought stress, whereas overexpressing SlGRAS4 ( SlGRAS4 -OE) in tomato enhanced tolerance of this stress. Under stress condition SlGRAS4 -OE plants accumulated much less ROS than wild-type and SlGRAS4 -RNAi plants. Numerous dehydration induced ROS-scavenging genes were upregulated in SlGRAS4 -OE plants after drought stress, implying that SlGRAS4 confers drought tolerance by modulating ROS homeostasis. On the other hand, there are several abscisic acid (ABA)-responsive elements in SlGRAS4 promoter, the relative expression of ABA signaling genes including SlPYLs, SlPP2Cs and SlSnRK2s were verified in WT and transgenic plants both under normal and drought stress, the changed drought sensitivity of transgenic plants was mainly caused by SlSnRK2s, the positive regulators of ABA signaling. Our results suggested that SlGRAS4 directly binds to and activates SlSnRK2.4 promoter, belongs to subclass III SnRK2s, which play crucial role in ABA signaling. Protein studies revealed that SlSnRK2.4 interacts with SlAREB1 and SlAREB2, the major downstream transcription factors of ABA-dependent signaling pathway. SlGRAS4 therefore confers drought tolerance may be through SnRK2-AREB pathway.